Exploitation in Duong Thu Huong’s Novel Without a Name and Viet Thanh Nguyen’s The Sympathizer - Liu, JingJie; Noor , Rohimmi (Journal of Studies in the English Language, 2025)
Unlike many studies that focus on distorted Marxist ideologies and diasporic identities in the postcolonial period, this study examines how characters in selected novels experience exploitation in respond to economic challenges, hierarchical military class divisions, and ideological transformations. The aim is to explore experienced by Quan and Luong from Novel Without a Name (1995), and the narrator and Man from The Sympathizer (2015), within the military system during the Vietnam War and its aftermath, as well as how these characters respond to the forces of oppression behind their exploitation. As salaried workers, soldiers function both as state employees and as vital components of the military apparatus that upholds the ruling class. Thus, they face exploitation from two sources: the state and the military system. These selected characters, as individuals within Vietnamese society, are compelled to participate in the nation’s historical process after the outbreak of the Vietnam War. They join the North Vietnamese military out of patriotism, loyalty, and aspirations for success. However, their enlistment does not reflect the full policies of a modern state; rather, it is coerced, driven by wartime needs and revolutionary ideals. By applying the conceptual framework of exploitation from Marxist theory, this study analyzes the characters’ interpersonal interactions and psychological struggles within their families, societies, and the military. It finds that the extent of their exploitation is determined by their military rank, assigned duties, and their role in society.